2017
DOI: 10.1055/s-0036-1597316
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy for Rectal Cancer

Abstract: It is evident that the use of laparoscopy in the management of rectal cancer has gained popularity in the last few years. It is still, however, not widely accepted as the standard of care. Multiple randomized trials have shown that short-term outcomes and perioperative morbidity and mortality of laparoscopic proctectomy are equivalent to open surgery. However, data regarding long-term oncologic outcomes are still scarce, with only a few randomized trials reporting similar outcomes in both laparoscopic and open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…[ 23 ] After several decades’ development, laparoscopic techniques have been advanced greatly, and many shortcomings have been overcome. [ 14 24 ] What's more, surgeons’ experience accumulation and progress in learning-curve can make them more skilful when operating LAS. In recent years, some articles reported that the long-time survival outcome of LAS was not inferior to open surgery for RC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] After several decades’ development, laparoscopic techniques have been advanced greatly, and many shortcomings have been overcome. [ 14 24 ] What's more, surgeons’ experience accumulation and progress in learning-curve can make them more skilful when operating LAS. In recent years, some articles reported that the long-time survival outcome of LAS was not inferior to open surgery for RC.…”
Section: Discussionmentioning
confidence: 99%
“…There is an on-going debate about the use of laparoscopic proctectomy for rectal cancer. Several randomized trials have shown that shortterm outcomes and perioperative morbidity and mortality of laparoscopic proctectomy in the management of rectal cancer are equivalent to open surgery [13]. Preservation of Denonvilliers' fascia during laparoscopic resection for mid-low rectal cancer effectively protects male urinary and sexual functions [14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, laparoscopic surgery can be performed safely in the elderly population, and reduce their pain and convalescence [2]. Therefore, laparoscopic technology has been routinely used in abdominoperineal excision (APE) in patients with distal rectal cancer [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%